KEMAMPUAN APRESIASI SASTRA SISWA SMA DI KOTA MEDAN - Rehan Halilah Lubis; Nurelide Nurelide (Balai Bahasa Sumatera Utara, 2019)
Literary learning systems have not used the ability to appreciate literature. Many teachers who teach literature only based on knowledge about teaching and learning activities feel monotonous and boring.In the 2013 curriculum, the literature learning system is always for students to appreciate literature based on literary text. Students ability to appreciate literary works is hoped to increase due to the application of the 2013 curriculum. However, there are so many students who have not been able to do it. The purpose of this research to find out the ability to appreciate student literature.theobjectives of the research method was carried out using quantitative descriptive method with a sample of 55 students from 3 schools in Medan City. The data collection technique is done by tests. Students are asked to answer questions about short stories entitled 'JuruMasak. The test refers to the students’ ability to understand literature based on the elements of literature and understand the use of language through literary work. The results of this study indicate that the average value of students' literary appreciation amounts to 88,465 and can be said to be good. While the value of the ability to understand language through literary works the value of the average ability to understand students' language amounts to 66,465. The value of 66,465 shows the results of the ability to understand student language quite well and still need to be improved